Understanding of Information Security Behavior of Social Media Users Among Millennial Generation - Djamen, Arje Cerullo; Lumapow, Harol R.; Lengkong , Jeffry Sony Junus; Rotty, Viktory Nicodemus Joufree (JR Education, 2022)
The increasing use of social networks in Indonesia is caused by the increasingly complete internet access facilities carried out by producers of communication service providers. This research aims to explain the information security behavior of the millennial generation of social media users. The population used in this research is the millennial generation. The sample used in this research is the millennial generation. Analysis using the Likert scale method. The results of this study show that social media has a significant and positive influence on social media security among the millennial generation. The results of this study also show that the behavior of the millennial generation in the context of information security is aware that information security is very important to pay attention to. In addition, this finding also shows that the millennial generation realizes that social media plays an important role in the communication and interactions that they undergo and realizes that there is a risk in the information contained in social media. This study suggests the millennial generation to keeps paying attention to information security when using social media.